'A Song is Not Just a Song': Community Mobilisation and Psychosocial Healing in South Africa's AIDS Crisis. Issue 3 (2nd October 2021) - Walker, Gavin Robert
ABSTRACT: South Africa has the highest number of HIV infections in the world, with more than five million people receiving anti-retroviral (ARV) therapies (UNAIDS 2019). However, during the early stages of the epidemic, there was no provision for ARVs through the state-run public health system, effectively limiting access to life-saving drugs. In response, the AIDS activist group the Treatment Action Campaign (TAC) and their HIV positive choir, The Generics, were established to mobilise South African civil society towards pressuring the government into deploying a national ARV programme. This article analyses and compares three culturally significant songs that were appropriated by The Generics. The analyses are socially and historically contextualised by interview data with current and former TAC members. The article suggests that songs facilitated collective mourning and psychosocial healing at a time when HIV treatments were largely unavailable. They further provided a catalyst for mobilisation that was steeped in the recent history of racial oppression against a virus that affected a disproportionate number of black South Africans. By appropriating struggle songs for their cause, The Generics tapped into emotional reservoirs of resistance culture to propel their agenda of government accountability and access to HIV medication.